INTERNATIONALIZATION IN HIGHER PROFESSIONAL EDUCATION IN RUSSIA: BACKGROUND, GEARS, INCENTIVES, LANGUAGE POLICY - Kira M. Inozemtseva (Высшее образование в России, 2016)
The article considers the background and conditions of reforming ESP teaching practice and ESP teachers’ retraining in non-linguistic universities in Russia.The factors of internationalization influence on Russian Higher Professional Education (HPE) competitiveness are listed, as well as professional risks of insufficient lingvo-professional competence. The role of university language policy in implementing the government strategy of HPE internationalization is determined.